2018
DOI: 10.3168/jds.2018-15071
|View full text |Cite
|
Sign up to set email alerts
|

The effects of source and concentration of dietary fiber, starch, and fatty acids on the daily patterns of feed intake, rumination, and rumen pH in dairy cows

Abstract: The daily patterns of feed intake and rumination influence rumen fermentation, rumen pH, and timing of absorbed nutrients in the dairy cow, but the effects of diet composition on these patterns are not well characterized. Data from 3 previously published experiments were examined to determine the influence of dietary starch, fiber, and fatty acids (FA) on daily patterns of intake, rumination, and rumen pH. Dietary neutral detergent fiber (NDF) and starch were investigated in 2 experiments, each with duplicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
3
25
0
1
Order By: Relevance
“…As expected, the tatty acid composition in pasture is characterized by the highest content of linolenic acid, which can influence the bio-hydrogenation process in the rumen leading the production of some intermediates (C18:2 trans 10, cis 12) that can depress the de novo synthesis of fatty acids in the mammary gland. These results are consistent with previous results in sheep and cows [ 15 , 16 ]. This response has been previously reported in dairy sheep fed fresh Italian ryegrass with a low level of NDF, as in the present study [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…As expected, the tatty acid composition in pasture is characterized by the highest content of linolenic acid, which can influence the bio-hydrogenation process in the rumen leading the production of some intermediates (C18:2 trans 10, cis 12) that can depress the de novo synthesis of fatty acids in the mammary gland. These results are consistent with previous results in sheep and cows [ 15 , 16 ]. This response has been previously reported in dairy sheep fed fresh Italian ryegrass with a low level of NDF, as in the present study [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…Figure 2 shows the patterns of rumination with ad libitum and restricted TMR. As anticipated, these are generally the inverse of eating times (Beauchemin et al, 1990;Sheahan et al, 2012;Salfer et al, 2018), with no marked differences in restricted or ad libitum feed availability except for the hours when feed was restricted. The TMR-restricted cows with or without hay ruminated for a large amount of time during the hours of TMR restriction.…”
Section: Limiting Total Mixed Ration Availability Alters Eating and Rumination Patterns Of Lactating Dairy Cowsmentioning
confidence: 52%
“…Attempts to spread out this pH fluctuation by feeding high-forage diets during the day and diets higher in carbohydrates in the evening have not been successful, as cows modified their feeding behaviors (Ying et al, 2015). In addition, studies have looked at altering these patterns of rumination and rumen pH by modifying fiber, starch type, and amount as well as content and source of fat with little effect (Salfer et al, 2018). Other studies have shown that cows appear to have the ability to modify their feeding behavior with rumen pH changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Los patrones de rumia han sido ampliamente estudiados en ganado lechero adulto (DeVries, von Keyserlingk, Weary, & Beauchemin, 2003;Krause & Oetzel, 2006;Hosseinkhani et al, 2008;Adin et al, 2009;Schirmann, von Keyserlingk, Weary, Veira, & Heuwieser, 2009) y asociados a niveles de consumo de materia seca (Hasegawa, Nishiwaki, Sugawara, & Ito, 1997), composición y forma física de la dieta (Yang, Beauchemin, & Rode, 2001;Maekawa, Beauchemin, & Christensen, 2002;Salfer, Morelli, Ying, Allen, & Harvatine, 2018), estro (Reith & Hoy, 2012), estado salud (Radostits, Gay, Hinchcliff, & Constable, 2007) y bienestar animal (Bristow & Holmes, 2007;Schirmann, von Keyserlingk, Weary, Veira, & Heuwieser, 2009;Soriani, Trevisi, & Calamari, 2012). Incluso existen en el mercado collares con sensores de sonido capaces de registrar automáticamente la rumia y generar alertas a los productores cuando esta disminuye (Sistema de monitoreo de rumia Hi-Tag, SCR Engineers Ltd., Netanya, Israel).…”
unclassified